The Influence of Learning Motivation, Teachers’ Instructional Strategies, and Learning Environment on Junior High School Students’ Writing and Speaking Skills - Siti Nafiyah; Sulistyaningsih; Eka Fadilah (International Journal of Science and Society, 2026)
The development of writing and speaking skills remains a major challenge in junior high school English education, particularly in contexts where students demonstrate varying levels of motivation, instructional exposure, and classroom support. Productive language skills require not only internal readiness but also effective pedagogical strategies and a conducive learning environment. This study aims to analyze the influence of learning motivation, teachers’ instructional strategies, and learning environment on junior high school students’ writing and speaking skills at SMPN 2 Sedati Sidoarjo. The research employed a quantitative explanatory design using Structural Equation Modeling based on Partial Least Squares (PLS-SEM) with SmartPLS 4. A total of 120 eighth-grade students participated in the survey through proportional random sampling. The findings reveal that teachers’ instructional strategies and learning environment have significant positive effects on writing and speaking skills, whereas learning motivation does not show a significant direct influence. The model demonstrates strong explanatory power in predicting students’ productive English competence. These results highlight the importance of pedagogical quality and supportive classroom climate in strengthening students’ communicative performance.